2013
DOI: 10.1039/c3ta12964k
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nanowire lithium-ion battery anodes with ALD deposited TiN coatings demonstrate a major improvement in cycling performance

Abstract: We demonstrate that nanometer-scale TiN coatings deposited by atomic layer deposition (ALD), and to a lesser extent by magnetron sputtering, will significantly improve the electrochemical cycling performance of silicon nanowire lithium-ion battery (LIB) anodes. A 5 nm thick ALD coating resulted in optimum cycling capacity retention (55% vs. 30% for the bare nanowire baseline, after 100 cycles) and coulombic efficiency (98% vs. 95%, at 50 cycles), also more than doubling the high rate capacity retention (e.g. 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 75 publications
3
93
0
Order By: Relevance
“…It is shown that silicon nanowire field effect transistors (SiNWFETs) [1][2][3] can be a reliable candid for biosensors which they are real-time, high selective and high sensitive [4][5][6]. They are also a nice choice for advanced energy storage and conversion devices [7] such as lithium-ion rechargeable batteries [8][9][10], photovoltaic devices [11][12][13], and thermoelectric devices [14][15][16]. Thermoelectric devices can convert heat (even waste heat) into electricity and vice versa and so they can be used for heating or cooling or for power generation.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that silicon nanowire field effect transistors (SiNWFETs) [1][2][3] can be a reliable candid for biosensors which they are real-time, high selective and high sensitive [4][5][6]. They are also a nice choice for advanced energy storage and conversion devices [7] such as lithium-ion rechargeable batteries [8][9][10], photovoltaic devices [11][12][13], and thermoelectric devices [14][15][16]. Thermoelectric devices can convert heat (even waste heat) into electricity and vice versa and so they can be used for heating or cooling or for power generation.…”
Section: Introductionmentioning
confidence: 99%
“…While atomic layer deposited TiN coatings have been studied and employed in various lithium-ion battery applications [53][54][55][56], there has been little to no research on their potential in the context of supercapacitors. Herein, we report a novel strategy to synthesize nanostructured NiCo2O4@TiN core-shell nanofiber arrays for high-performance supercapacitors with significantly improved rate capability and electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Silicon nanoparticles (Si NPs) have been found to tolerate extreme changes in volume with cycling. [ 13 ] Hence, great efforts have been made to improve the cycling stability and electrical conductivity by using various Si-based nanostructures, including Si nanowires, [ 3,14,15 ] porous Si, [16][17][18][19] and conductive agent coated Si such as carbon, [ 18,20,21 ] Ag, [ 22,23 ] and conducting polymer. [ 24 ] Among them, a yolkshell-structured carbon@void@silicon (CVS) composite [ 25,26 ] is quite promising for practical applications, because the void space between the outer carbon shell and the inside Si NP allows the room for volume changes of Si NP without deforming the carbon shell and SEI fi lm, which in turn allows for the growth of a stable SEI on the surface of the outer carbon shell.…”
Section: Introductionmentioning
confidence: 99%